A Computational Study on a Strategy for Isolating a Stable Cyclopentadienyl Cation. Issue 43 (10th September 2014) - Iversen, Kalon J.; Wilson, David J. D.; Dutton, Jason L.
Abstract A computational study has been carried out to examine the feasibility of generating a simple monocyclic cyclopentadienyl cation that may be sufficiently stable to isolate and handle at ambient temperatures. Using judicious placement of electron‐withdrawing groups (CF3) about the ring we have identified a derivative that may approach the stability of isolobal (and isolatable) borole rings, as evaluated by HOMO–LUMO and singlet–triplet gaps. These Cp+ derivatives may therefore be an attractive target for synthetic isolation.